The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/bg-12-4543-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mesozooplankton structure and functioning during the onset of the Kerguelen phytoplankton bloom during the KEOPS2 survey

Abstract: Abstract. This paper presents results on the spatial and temporal distribution patterns of mesozooplankton in the naturally fertilized region to the east of the Kerguelen Islands (Southern Ocean) visited at early bloom stage during the KEOPS2 survey (15 October to 20 November 2011). The aim of this study was to compare the zooplankton response in contrasted environments localized over the Kerguelen Plateau in waters of the east shelf and shelf edge and in productive oceanic deep waters characterized by conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 44 publications
(67 reference statements)
2
39
0
Order By: Relevance
“…Values of carbon content in cylindrical fecal pellets found in the literature range over approximately 1 order of magnitude between 0.01 and 0.1 mg C mm −3 (González and Smetacek, 1994;González et al, 1994González et al, , 2000Carroll et al, 1998), leading to potential strong variations in carbon flux estimations if large volumes of fecal pellets are involved, as was the case at E-5. Mesozooplankton communities collected in Bongo nets from 250 m to the surface (day and night haulings, except at R-2 and F-L, where only day haulings were conducted), and analysed with a ZooScan integrated system (Carlotti et al, 2015), generally revealed a large dominance of the size fraction 500-1000 µm with values from 54 to 79 % (considering only the stations where the traps were deployed). Microscopic identifications confirmed a community largely dominated by copepods (Carlotti et al, 2015).…”
Section: Comparison Of Poc Flux Estimationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Values of carbon content in cylindrical fecal pellets found in the literature range over approximately 1 order of magnitude between 0.01 and 0.1 mg C mm −3 (González and Smetacek, 1994;González et al, 1994González et al, , 2000Carroll et al, 1998), leading to potential strong variations in carbon flux estimations if large volumes of fecal pellets are involved, as was the case at E-5. Mesozooplankton communities collected in Bongo nets from 250 m to the surface (day and night haulings, except at R-2 and F-L, where only day haulings were conducted), and analysed with a ZooScan integrated system (Carlotti et al, 2015), generally revealed a large dominance of the size fraction 500-1000 µm with values from 54 to 79 % (considering only the stations where the traps were deployed). Microscopic identifications confirmed a community largely dominated by copepods (Carlotti et al, 2015).…”
Section: Comparison Of Poc Flux Estimationsmentioning
confidence: 99%
“…Mesozooplankton communities collected in Bongo nets from 250 m to the surface (day and night haulings, except at R-2 and F-L, where only day haulings were conducted), and analysed with a ZooScan integrated system (Carlotti et al, 2015), generally revealed a large dominance of the size fraction 500-1000 µm with values from 54 to 79 % (considering only the stations where the traps were deployed). Microscopic identifications confirmed a community largely dominated by copepods (Carlotti et al, 2015). However, most of the fecal pellets collected in gel traps at E-5 were large fragments (Fig.…”
Section: Comparison Of Poc Flux Estimationsmentioning
confidence: 99%
See 3 more Smart Citations